Assessing the outcome of patients with liver cirrhosis during hospital stay: A comparison of lymphocyte/monocyte ratio with MELD and Child-Pugh scores - Jamil, Zubia; Durrani, Asghar Aurangzeb (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Developing an easy and reliable score for evaluating the prognosis of patients with liver cirrhosis has always been challenging for hepatologists. This study aimed to assess the lymphocyte-to-monocyte ratio (LMR) in comparison with the Model for End-Stage Liver Disease (MELD) and Child-Pugh (CP) scores for determining the outcomes in these patients during hospital stay. Materials and Methods: Receiver operator characteristic (ROC) curve was used to assess the efficacy of three parameters (LMR and MELD and CP scores) in determining the outcomes in 182 patients with cirrhosis. The cutoff values were calculated using Youden index, and the area under the curves (AUCs) was also compared. The associations of these scores between the survived and nonsurvived group was studied. The predictors of patient survival were determined using logistic regression analysis. Results: The mean values for LMR and MELD and CP scores were 6.23, 11.62, and 9.32, respectively. MELD and CP were positively correlated with each other. LMR was negatively correlated to both MELD and CP scores (p=0.04). Pairwise comparison showed that the difference between the AUCs of MELD and LMR was not statistically significant (0.958 vs. 0.807; p>0.05). With the LMR cutoff value of Conclusion: LMR can be used to determine the outcome of patients during hospital stay, because it is easy to calculate and can be interpreted with efficacy nearly equal to those of MELD and CP scores. Cite this article as: Jamil Z, Durrani AA. Assessing the outcome of patients with liver cirrhosis during hospital stay: A comparison of lymphocyte/monocyte ratio with MELD and Child-Pugh scores. Turk J Gastroenterol 2018; 29: 308-15.